Analisis Model Pelayanan Pendidikan Bagi Anak Disleksia dan Disgrafia di Sekolah Inklusi SDN Meruya Selatan 06 Pagi - Nurfadhillah, Septy; Adella, Adella; Asfari, Ahmad Iklil; Anggraeny, Devie; Sari, Nicken Novita; Ananda, Virania (MASALIQ, 2022)
This study aims to determine the implementation of the curriculum, learning mechanisms, as well as the difficulties of students learning to read (dyslexia) and the difficulties of students learning to write (dysgraphia). The method used in this research is qualitative research with descriptive method. Children with learning disabilities are children who experience difficulties in their academic tasks, which are caused by a minimal dysfunction of the brain, or in basic psychology, so that their learning achievements do not match their actual potential. Children who have learning difficulties, both in general and in particular, such as dyslexia and dysgraphia, need special education services in their learning process at school. The results of this study indicate that the curriculum used is the 2013 curriculum but for children with special needs, dyslexia and dysgraphia need some minor adjustments. in the curriculum structure used, such as simplification of existing learning indicators. In the learning mechanism, children with dyslexia and dysgraphia receive special services in the form of additional learning outside of general lesson hours. Children with special needs, dyslexia and dysgraphia, need an adjustment in learning that prioritizes audio-visual. In terms of educational services, the learning and managerial education system uses regular student policies but is simplified according to the needs of children with special needs, dyslexia and dysgraphia.